2019
DOI: 10.15252/embj.2018100852
|View full text |Cite
|
Sign up to set email alerts
|

Mammary stem cells and progenitors: targeting the roots of breast cancer for prevention

Abstract: Breast cancer prevention is daunting, yet not an unsurmountable goal. Mammary stem and progenitors have been proposed as the cells‐of‐origin in breast cancer. Here, we present the concept of limiting these breast cancer precursors as a risk reduction approach in high‐risk women. A wealth of information now exists for phenotypic and functional characterization of mammary stem and progenitor cells in mouse and human. Recent work has also revealed the hormonal regulation of stem/progenitor dynamics as well as int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 220 publications
(323 reference statements)
5
75
0
Order By: Relevance
“…That is, genome states that were associated with cancer arise before any detectable cancer exists. In the context of previous transcriptome profiling that showed ER+ luminal-subtype cancers have similar profiles to those of mature luminal cells [Tharmapalan et al, 2019], we speculate that we have identified an epigenetic mechanism to explain why luminal-subtype cancers have higher incidence in older women. That is, genes for key epigenetic regulatory proteins are themselves epigenetically regulated with age, including hypomethylation of CXXC5 at a PPR that is enriched for ESR1 binding motifs.…”
Section: Discussionsupporting
confidence: 50%
“…That is, genome states that were associated with cancer arise before any detectable cancer exists. In the context of previous transcriptome profiling that showed ER+ luminal-subtype cancers have similar profiles to those of mature luminal cells [Tharmapalan et al, 2019], we speculate that we have identified an epigenetic mechanism to explain why luminal-subtype cancers have higher incidence in older women. That is, genes for key epigenetic regulatory proteins are themselves epigenetically regulated with age, including hypomethylation of CXXC5 at a PPR that is enriched for ESR1 binding motifs.…”
Section: Discussionsupporting
confidence: 50%
“…The molecular mechanisms governing the differentiation of mammary cells are not well understood, but the process involves bipotent stem cells differentiating into unipotent progenitors, and subsequently to luminal, alveolar or myoepithelial cells. While giving rise to lobuloalveolar epithelial cells, stem and progenitor cells are also considered the cell-of-origin in breast cancer [ 21 ]. It has been suggested that breast cancer mainly originates in these undifferentiated cells within the terminal duct of a lobular unit, which are most vulnerable to carcinogenesis [ 10 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous signaling pathways involved in healthy development have been implicated in BCa progression. These pathways are often linked to cell proliferation, apoptosis, differentiation, and motility [ 16 ]. Three significant pathways govern mammary gland and BCa stem cell development: (1) estrogen receptor (ER) signaling; (2) HER2 signaling; and (3) canonical Wnt signaling.…”
Section: Introductionmentioning
confidence: 99%